Perbaikan Sistem Prototype Part Order pada Divisi PPMO di PT. TMMIN - Bertinus Enrico Rahardjo; Benedictus Rahardjo (Jurnal Titra, 2020)
Globalization cause business improve rapidly. PT Toyota Motor Manufacturing Indonesia (PT TMMIN) which is an automotive company also need to innovate and keep improving. Innovation needed a prototype before development part going live. Prototype part evaluation done at Toyota Daihatsu Engineering & Manufacturing (TDEM) in Thailand and TMC so PT TMMIN need to export part according to order given. Order is divided into two group which are special project and general project. Special project is project based on vehicle produced by PT TMMIN and general project is project based on general Toyota vehicle. One of system issue is no special budget number dedicated to TWX-21 System. Currently, TWX-21 System is using special project based budget so budget amount depends on ongoing special project. Thinking framework used is Toyota Business Practice (TBP). The purpose is to find out the reason for the lack of a dedicated budget number for the TWX-21 System. The improvements have a positive effect, which are a single dedicated budget created for TWX-21 System.